Policy-Based Local Economic Analysis: A Study of the Impact of the MBG Program on MSMEs at SMP Negeri 10 Bandar Lampung - Indri Maheswari; Bagus Andika Prastian; Shabrina Hidayatullaila; Zoraya Kartika Ekanusa; Nabila Sagita; Bintang Putra Nandika (Pattimura Proceeding, 2026)
This research examines the influence of the Makan Bergizi Gratis (MBG) program initiated by President Prabowo Subianto on the local school-based economy, particularly canteens and micro food enterprises. The research stems from the concern that although MBG aims to improve students’ nutritional intake and learning concentration, its economic impact on surrounding businesses remains unclear. The purpose of this study is to explore how the program affects business income levels, students’ purchasing behavior, and the economic sustainability of small traders operating near schools. A qualitative approach was employed through open-ended interviews with school canteen managers, micro-enterprise food vendors, and stakeholders involved in food distribution. The findings reveal that most micro-enterprises experienced a decline in income because students no longer purchase food independently as they did before the implementation of MBG. These results imply that the program should not only focus on nutritional benefits for students but also involve local economic actors in the food supply chain to ensure that MBG contributes simultaneously to student welfare and community economic sustainability.